2007
DOI: 10.1021/bi700662d
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Nitrosyl Adduct of Substrate-Bound Mouse Cysteine Dioxygenase by Electron Paramagnetic Resonance:  Electronic Structure of the Active Site and Mechanistic Implications

Abstract: Mammalian cysteine dioxygenase (CDO) is a non-heme iron metalloenzyme that catalyzes the first committed step in oxidative cysteine catabolism. The active site coordination of CDO comprises a mononuclear iron ligated by the Nepsilon atoms of three protein-derived histidines, thus representing a new variant on the 2-histidine-1-carboxylate (2H1C) facial triad motif. Nitric oxide was used as a spectroscopic probe in investigating the order of substrate-O2 binding by EPR spectroscopy. In these experiments, CDO ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
233
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(253 citation statements)
references
References 74 publications
(136 reference statements)
19
233
1
Order By: Relevance
“…Pierce et al (29) recently reported that, in the absence of cysteine, the iron metallocenter of CDO is essentially unreactive to NO (used as a surrogate probe for O 2 ). Binding of NO, however, is greatly facilitated when CDO is incubated in the presence of cysteine.…”
Section: Discussionmentioning
confidence: 99%
“…Pierce et al (29) recently reported that, in the absence of cysteine, the iron metallocenter of CDO is essentially unreactive to NO (used as a surrogate probe for O 2 ). Binding of NO, however, is greatly facilitated when CDO is incubated in the presence of cysteine.…”
Section: Discussionmentioning
confidence: 99%
“…An iron content of 0.42 Ϯ 0.028 mol Fe(II) per mol CdoB was determined by the method of Pierce et al (9). Also, Fe(III) could be detected in the purified His 6 -tagged CdoB at 0.048 Ϯ 0.024 mol Fe(III) per mol enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…Determination of the iron content was done with bathophenanthroline disulfonic acid disodium salt (BP-DADS), based on the method of Pierce et al (9).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations